The impact of cognitive load on operatic singers' timing performance - Çorlu, Muzaffer; Maes, Pieter-Jan; Muller, Chris; Kochman, Katty; Leman, Marc (Frontiers in Psychology, 2015)
In the present paper, we report the results of an empirical study on the effects of cognitive load on operatic singing. The main aim of the study was to investigate to what extent a working memory task affected the timing of operatic singers’ performance. Thereby, we focused on singers’ tendency to speed up, or slow down their performance of musical phrases and pauses. Twelve professional operatic singers were asked to perform an operatic aria three times; once without an additional working memory task, once with a concurrent working memory task (counting shapes on a computer screen), and once with a relatively more difficult working memory task (more shapes to be counted appearing one after another). The results show that, in general, singers speeded up their performance under heightened cognitive load. Interestingly, this effect was more pronounced in pauses – more in particular longer pauses – compared to musical phrases. We discuss the role of sensorimotor control and feedback processes in musical timing to explain these findings.